2020
DOI: 10.1111/ijcp.13646
|View full text |Cite
|
Sign up to set email alerts
|

How many patients with heart failure are eligible for cardiac contractility modulation therapy?

Abstract: Background Increasing evidence exists suggesting that cardiac contractility modulation therapy (CCM) improves symptoms in heart failure patients if various selection criteria are fulfilled. The aim of this study is to analyse an unselected sample of heart failure patients to establish what percentage of patients would meet the current criteria for CCM therapy. Methods All patients admitted to two district general hospitals in the UK in 2018 with a diagnosis of heart failure were audited for eligibility for CCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Initially, designed for treating patients with sinus rhythm and narrow QRS, CCM has expanded its applications to include those suffering from atrial fibrillation (AF) and patients with wide QRS that do not respond to CRT 16 . Patients can be considered for CCM therapy if they meet the following criteria: (a) ejection fraction (EF) between 25% and 45%; (b) QRS duration less than 130 ms, ; (c) New York Heart Association (NYHA) class 3 or 4; and (d) history of HF treated with stable medications for at least 90 days 30 . However, patients with significant valvular disease, permanent or persistent AF, use of a biventricular pacemaker, QRS duration exceeding 130 ms, or those undergoing palliative treatment are not suitable candidates for CCM therapy 30 .…”
Section: Cardiac Contractility Modulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, designed for treating patients with sinus rhythm and narrow QRS, CCM has expanded its applications to include those suffering from atrial fibrillation (AF) and patients with wide QRS that do not respond to CRT 16 . Patients can be considered for CCM therapy if they meet the following criteria: (a) ejection fraction (EF) between 25% and 45%; (b) QRS duration less than 130 ms, ; (c) New York Heart Association (NYHA) class 3 or 4; and (d) history of HF treated with stable medications for at least 90 days 30 . However, patients with significant valvular disease, permanent or persistent AF, use of a biventricular pacemaker, QRS duration exceeding 130 ms, or those undergoing palliative treatment are not suitable candidates for CCM therapy 30 .…”
Section: Cardiac Contractility Modulationmentioning
confidence: 99%
“…Patients can be considered for CCM therapy if they meet the following criteria: (a) ejection fraction (EF) between 25% and 45%; (b) QRS duration less than 130 ms, ; (c) New York Heart Association (NYHA) class 3 or 4; and (d) history of HF treated with stable medications for at least 90 days 30 . However, patients with significant valvular disease, permanent or persistent AF, use of a biventricular pacemaker, QRS duration exceeding 130 ms, or those undergoing palliative treatment are not suitable candidates for CCM therapy 30 . CCM has proven to be safe and effective for patients with a narrow QRS (approximately 130 ms), EF between 25% and 45%, and moderate‐to‐severe symptomatic HF with EF of 25–45% 29 .…”
Section: Cardiac Contractility Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 5.2% (n=33) of our patients met the indication criteria, and about one-third (n=10) of them would be eligible for a CCM as a second device additional to another cardiac implantable electronic device implanted previously. In the analysis of Dulai et al 5.1% of the examined cohort of hospitalized HF patients were suitable for CCM therapy 135 . A previous review article from Abi-Samra estimated that 79% of patients with NYHA II-III and LVEF<35% could be eligible for CCM 136 .…”
Section: The Eligibility For Cardiac Contractility Modulationmentioning
confidence: 97%